FAKTOR YANG MEMENGARUHI KEJADIAN HIPERTENSI PADA UMUR 30 – 40 TAHUN DI WILAYAH KERJA PUSKESMAS PALANRO KABUPATEN BARRU - Gerhana Waty Gerhana Waty (Bina Generasi : Jurnal Kesehatan, 2022)
Hypertension is still a public health problem in Indonesia considering it is high prevalence.Hypertension can cause complications such as heart disease,stroke,and kidney failure.Hypertension arises due to the interaction of various factors that influence.The purpose of this research was to determine the factors that influence the incidence of hypertension at the age of 30-40 years in the work area of the Palanro Public Health Center,Barru Regency.The design of this research used an analytic cross sectional study design with accidental sampling technique with a total sample of 82 respondents.The variables studied were diabetes,physical activity,stress,smoking habits,and salt intake patterns. Based on the results of the research,it was found that diabetes with p 0,014 ,physical activity with p 0,028 ,stress with p 0,001 ,smoking habits with p 0,005 are factors that influence the accidence of hypertension at the age 30-40 years in the work area of the Palanro Public Health Center,Barru Regency. Salt intake pattern with p 0,771 was not an influencing factor.The results of multivariate analysis showed that diabetes,stress,and smoking habits were the most influential factors.Conclusion : diabetes,physical activity,stress,smoking habits,are factors that influence the incidence of hypertension at the age of 30-40 years in the work area of the Palanro Public Health Center,Barru Regency.